Automated Face Recognition Attendance System for Students in Universiti Teknologi PETRONAS (UTP) - Ganesh, Pavinthran (IRC, 2019)
Automated Face Recognition Attendance System is a system where it can perform two basic tasks of identification and verification of a person. This report covers the studies made on the technologies that can be used to develop a reliable attendance system for Universiti Teknologi Petronas (UTP). The main reason of this project is to come up with the better attendance system in UTP that can be used to minimize the cheating activities among students in recording the attendance. Moreover, the main objective of this project is to create a reliable and flexibility method of recording attendance where it will send an automation email to the students’ parents if the students’ attendance is less than 80%. The current system that Universiti Teknologi PETRONAS(UTP) is using QR code attendance system where the students need to scan QR code that lecturer provides and put their attendance in the form and their attendance will be recorded. Moreover, UTP is still using the traditional method where students need to put their attendance on a piece of paper. Thus, there is a problem in these both methods where students are cheating by sending the QR code links to their friends who are not attending the class and they are marking attendance on behalf of their friends. Moreover, it consists large consumption of papers and higher consumption of time to record the attendance. This system will be designed by using agile methodology because agile methodology is the most iterative, priority based and simple.Moreover, changes for requirement can be done in any phases in agile methodology. Besides, recognition of image extraction knowledge is expected to utilize the neural network in order to ease the development process. In addition, knowledge on requiredalgorithms and techniques are described in this report too. Moreover, preliminary survey has been done during requirement gathering phase. The results of the survey have proven that there is need of replacement in current method of student attendance system for the betterment of UTP students.